Physical exercise of women after menopause - Piotrowska, Sylwia; Majchrzycki, Marian (Menopause Review/Przegląd Menopauzalny, 2013)
Menopause is a natural process affecting all women. Psychological and physical changes associated with this process can appear before and for a long time after menopause. Some women experience mild symptoms whereas others experience more intense ones. Physical exercises positively affect the changes occurring in women after menopause. They help reduce the levels of triglycerides, glucose concentration and insulin. Arterial blood pressure and BMI are lowered. Blood circulation in brain and the levels of HDL improve. Average bone density in people who exercise is higher than in people who do not exercise. Thanks to modifications brought upon by physical activity in the female body, it is easier to fight obesity, osteoporosis and their results. Exercises reduce the risk of the metabolic syndrome, breast and endometrial cancer. Lowered quality of life caused by menopause-related dysfunctions and aging increases in people who are physically active. All women after menopause are advised to pick up physical exercises in their free time.